2023
DOI: 10.5194/aab-66-51-2023
|View full text |Cite
|
Sign up to set email alerts
|

Sex effect on the fatty acid profile and chemical composition of meat from beef cattle fed a whole shelled corn diet

Abstract: Abstract. This study aimed to evaluate the effect of sex on the chemical composition, fatty acid profile, and nutritional indexes of the Longissimus lumborum muscle of feedlot cattle fed a whole shelled corn diet. A total of 40 Nellore cattle were used, of which 20 animals were uncastrated bulls and 20 were heifers, with an average body weight of 411 ± 20.82 and 274 ± 17.80 kg, respectively. The diet was composed of 85 % whole shelled corn and 15 % protein–vitamin–mineral supplement. The chemical composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
3
3
0
Order By: Relevance
“…In the study moisture values determined from beef were similar to the values found in other studies (Ngom et al, 2022;Salim et al, 2023;Santana et al, 2023). However, the moisture value in Korean Hanwoo cattle was reported to be lower (69.21%) than the determined value (Bostami et al, 2023).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In the study moisture values determined from beef were similar to the values found in other studies (Ngom et al, 2022;Salim et al, 2023;Santana et al, 2023). However, the moisture value in Korean Hanwoo cattle was reported to be lower (69.21%) than the determined value (Bostami et al, 2023).…”
Section: Resultssupporting
confidence: 86%
“…The protein values found for cattle in the study were similar to some of the values found in the researches (Hamed Hammad Mohammed et al, 2020;Pouzo et al, 2023;Santana et al, 2023), higher than some (Salim et al, 2023) and lower than some (Oliveira et al, 2021;Ngom et al, 2022). While the values reported for sheep were in agreement with (Costa et al, 2009;Romero-Bernal et al, 2017;Radzik-rant et al, 2023) or higher than literature reports and findings (Mioč et al, 2007;Lima et al, 2022;Latoch et al, 2023;Lunesu et al, 2023;Uushona et al, 2023).…”
Section: Figure 2 Ash Content Of Meat Samples Obtained From Different...supporting
confidence: 88%
See 2 more Smart Citations
“…Palmitic acid (C16:0) and stearic acid (C18:0) were beef's most prominent saturated fatty acids. In contrast, oleic acid (C18:1n9c) was the predominant unsaturated fatty acid, a finding consistent with the study of Santana et al (2023). It has been reported that fatty acid compositions are different depending on breed.…”
Section: Fatty Acid Profile In Different Breedssupporting
confidence: 90%